2020
DOI: 10.26656/fr.2017.4(6).324
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive monolaurin as an antimicrobial and its potential to improve the immune system and against COVID-19: a review

Abstract: Monolaurin is monoacylglycerol which is a bioactive lipid since it can affect the human biological systems. This review discusses the bioactive properties of monolaurin, especially its role as an antibacterial, immune system enhancement, and its ability as an antiviral so that it has the potential to fight against various viral attacks. Monolaurin can act as an antibacterial in inhibiting the growth of several pathogenic bacteria, especially gram-positive bacteria. Monolaurin is known to be able to enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…The monolaurin from the synthesis has a high emulsion capacity of 93.66% and stability of 89.54%. Therefore, monolaurin has been widely used in emulsions, specifically microemulsions [ 34 ]. Zhang et al found the emulsion stability of monolaurin was 95% at 2 h and 85% at 24 h [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The monolaurin from the synthesis has a high emulsion capacity of 93.66% and stability of 89.54%. Therefore, monolaurin has been widely used in emulsions, specifically microemulsions [ 34 ]. Zhang et al found the emulsion stability of monolaurin was 95% at 2 h and 85% at 24 h [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Monolaurin has a broad-spectrum activity as an antibacterial, boosts the immune system, and acts as an anti-viral. Its ability to kill various types of viruses, especially enveloped viruses such as influenza viruses and coronavirus 229E, makes monolaurin potentially able to ward off SARS-CoV-2 which is the cause of the COVID-19 ( Subroto, & Indiarto, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These lymphocytes mark the incoming antigen and then destroy it. Thus, the immune system is the human body's mechanism to fight or expel foreign objects that enter their bodies in the form of bacteria or viruses (Catanzaro et al, 2018;Subroto and Indiarto, 2020).…”
Section: The Potential Of Garlic To Improve the Immune Systemmentioning
confidence: 99%